A Survey of Autoantibodies to Self Antigens in Graves' Disease Patients with Thyroid-Associated Ophthalmopathy. (May 2013) - Bei, R.; Romano, M.; Caputo, M.P.; Sconocchia, G.; Capuani, B.; Coppola, A.; Nucci, C.; Pastore, D.; Bellia, A.; Mancino, R.; Andreadi, K.; Cerilli, M.; et al.
Thyroid Associated Ophthalmopathy (TAO) is a complex pathology to treat and a considerable threat for Graves' Disease (GD) patients. Thus, there is great interest to find tools able to predict the onset and prognosis of TAO. Chronic inflamed tissues are characterized by tissue damage and recruitment of cells from the bloodstream, events that can lead to self-antigen exposure and induce autoimmune phenomena. In this study, we determined whether the occurrence of antibody anti-extracellular matrix (ECM) molecules [Collagen CI, CIII, CIV, CV, laminin (LM) and fibronectin, (FN)], anti-smooth muscle (ASM), anti-nuclear antigen (ANA), anti-ribonucleoprotein (RNP) and anti-thyroid-stimulating hormone (TSH) receptor (TRAbs) were associated with TAO in GD patients. We analyzed serum of 50 patients affected by GD, 24 of whom were affected by TAO, and 40 healthy donors (HD). The occurrence of TRAbs or ANA, anti-SM and anti-RNP antibodies did not allow to discriminate TAO+ from TAO- GD patients. Among the 24 TAO+ and 26 TAO- patients, 15/24 and 17/26 displayed TRAbs, respectively. None of the GD patients displayed anti-RNP antibodies, while 20/24 TAO+ and 17/26 TAO- patients were found to be positive for ANA and 3/24 TAO+ and 4/26 TAO- patients showed anti-SM antibodies. Conversely, when compared with HD control sera, GD sera showed antibodies to all individual ECM molecules. Remarkably, anti-CHI autoantibodies of the IgG isotype were significantly associated with GD TAO+ patients (p=0.045). Indeed, 6 out of 24 GD TAO+ patients scored positive for anti-CIII IgGs as compared to only 1 out of 26 TAO-. Our results suggest the potential involvement of anti-ECM antibodies in GD and a contribution of anti-CIII IgGs in TAO pathogenesis of GD patients.